Bismuth induced encephalopathy caused by tri potassium dicitrato bismuthate in a patient with chronic renal failure. Issue 3 (March 1990) - Playford, R J; Matthews, C H; Campbell, M J; Delves, H T; Hla, K K; Hodgson, H J; Calam, J
Abstract : A 68 year old man with a creatinine clearance rate of only 15 ml/min took twice the recommended dose of tripotassium dicitrato bismuthate (TDB) as DeNol liquid; 10 ml qds; a total of 864 mg bismuth daily for two months. Whole blood bismuth concentrations rose to 880 micrograms/l and he developed global cerebral dysfunction with hallucinations, ataxia, and an abnormal EEG. Renal clearance of bismuth rose from 0.24 to 2.4 ml/min when the heavy metal chelator 2-3 dimercapto-1 propane sulphonic acid (DMPS) was given by mouth. Bismuth was measured by a novel method involving inductively coupled plasma source mass spectrometry. Fifty days after stopping TDB, whole blood bismuth concentrations fell to 46 micrograms/l and the patient's EEG returned to normal. His mental function also recovered completely. The case serves as a timely reminder that TDB should not be administered to patients with renal disorders, as stated in the data sheet.